The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4236/ojpchem.2015.54007
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Plastics in Seawater in Laboratory

Abstract: Degradable plastics are used as a way to decrease the environmental impact of these materials when they become waste. However, they can reach natural ecosystems due to littering and bad management. This research assesses the performance of oxodegradable and compostable plastics on marine environments through a respirometric lab test. Probes of the plastics, with and without previous simulated weathering, were put in contact for 48 days with a marine inoculum, in a system that guarantees continuous aeration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…To complete this study a characterization of the microorganisms diversity would have been important to better understand the mechanisms of PHBV biodegradation in seawater. Differences in the oxidation degree of the polymers, in the environmental conditions or in the methodologies used are also important factors that may explain controversary results showing ever no significant proof of mineralization of pre-oxidized OXO in marine water ( Alvarez-Zeferino et al, 2015 ) or clear biodegradation in other environments ( Jakubowicz, 2003 ; Chiellini et al, 2007 ; Ojeda et al, 2009 ; Yashchuk et al, 2012 ; Eyheraguibel et al, 2018 ). Giving the fact that relatively few studies focused on colonization of plastic at sea, this study should help further researches on biodegradability of plastics in marine habitats.…”
Section: Discussionmentioning
confidence: 99%
“…To complete this study a characterization of the microorganisms diversity would have been important to better understand the mechanisms of PHBV biodegradation in seawater. Differences in the oxidation degree of the polymers, in the environmental conditions or in the methodologies used are also important factors that may explain controversary results showing ever no significant proof of mineralization of pre-oxidized OXO in marine water ( Alvarez-Zeferino et al, 2015 ) or clear biodegradation in other environments ( Jakubowicz, 2003 ; Chiellini et al, 2007 ; Ojeda et al, 2009 ; Yashchuk et al, 2012 ; Eyheraguibel et al, 2018 ). Giving the fact that relatively few studies focused on colonization of plastic at sea, this study should help further researches on biodegradability of plastics in marine habitats.…”
Section: Discussionmentioning
confidence: 99%
“…In SNI 7818: 2014 and SNI 7188.7.2011, it was stated that one of the degradability tests for plastic is by using tensile strength test and it was also supported by ISO 527-3 (Lucas et al, 2008, Alvarez-zeferino et al, 2015, Guo Meng et al, 2016, Hoffmann et al, 1994, Hongliang et al, 2017, Strapasson et al, 2005. Tensile strength tests were conducted by tensile meter (Brookfield CT3 -4500) which were carried out on plastic before and after treatment by Spirulina sp.…”
Section: Tensile Strength Measurementmentioning
confidence: 99%
“…One may speculate that either the plastic could serve as a support for microbial growth (Characklis and D Bryes, 2009; Peyton and Characklis, 1995; Stoodley et al, 2002), thus enhancing the dark fermentation process of the degradable material (Poggi-Varaldo et al, 2009, 2012), or that the plastics present in the WD could be at least partially degradable. Microorganisms capable of degrading these materials in a variety of environments were reported (Alvarez-Zeferino et al, 2015; Shimao, 2001; Sivan, 2011; Tokiwa et al, 2009), nevertheless further investigation should be performed to test this hypothesis. Recent studies have found the presence of colonies of microbes found in some micro-plastics in the ocean (Samoray, 2016).…”
Section: Resultsmentioning
confidence: 99%